Model komunikasi pemasaran kopi tuku sebagai resilensi covid-19: sebuah analisis isi - Firdaus, Muhamad Azis; Daeng GS, Achmad; Indrawati, Indrawati; Lapoliwa, Gerdha Erlinda Sari; Chin, Jacky (Jurnal Komunikasi Profesional, 2021)
Due to recent technological advances, marketing strategies have shifted from conventional to online. Traditional businesses use this digital marketing strategy because it is considered no more effective than other forms of marketing, such as using brochures and catalogs. Kopi Tuku as a business that mushroomed first during the Covid-19 pandemic, used digital marketing strategies to introduce digital products, one of which was social media. This is because social media is a platform that allows people to communicate information in the form of text, photos, videos, and audio with each other and with businesses, or vice versa. This study aims to find out how Kopi Tuku's digital marketing strategy during the Covid-19 pandemic uses content analysis. The method used is Krippendorff's content analysis via Instagram @tokokopituku for the period January 1, 2021 to September 30, 2021. The conclusion of this study is that Kopi Tuku's marketing strategy is more of an advertising strategy that highlights related information about Kopi Tuku.